Optimising 'Lambe Hoaks' Digital Literacy to Strengthen National Resilience Against Hoaxes - Putra, Fadhil A.; Samad, M. Yusuf; Mulyadi (Jurnal Lemhannas RI, 2024)
Purpose: The spread of hoaxes has intensified in recent years, posing a threat to national resilience due to their potential to incite national disintegration. This study aims to optimise the "Lambe Hoaks" digital literacy program on Instagram to mitigate the spread of misinformation and strengthen national resilience. Study Design/Methodology/Approach: This research employs a qualitative approach, gathering data through interviews with key informants from both the governmental and private sectors. The analysis focuses on assessing the effectiveness of the "Lambe Hoaks" programme and identifying strategies for improvement. Findings: The "Lambe Hoaks" programme, which combines contemporary appeal with accurate information dissemination, holds significant potential to serve as a primary reference for the public in verifying information. However, findings reveal a gap between the programme's objectives and its actual impact. Addressing this discrepancy requires enhancements to content quality, increased audience engagement, and the implementation of a more effective promotional strategy. Originality/Value: This study provides a focused analysis of the "Lambe Hoaks" initiative, highlighting its potential and limitations in combating hoaxes. It offers practical recommendations for optimising digital literacy efforts to safeguard national resilience, enriching the discourse on countering misinformation in the digital age.